Woman of Tokyo Based on a Novel by Ernst Schwarz - Hughes, Ed; Schwarz, Ernst (The Ozu Collection, 2012)
In a poor, working class district of Tokyo, a woman named Chikako Shimamura (Yoshiko Okada) shares a modest apartment with her younger brother, Ryoichi (Ureo Egawa). Despite seemingly insurmountable economic hardship, Chikako has managed to make ends meet, working every day in her full-time employment as an office typist, and every evening on commissioned translations for a university professor. Her constant toil, filial devotion, and personal sacrifice afford Ryoichi the privilege of devoting himself completely to his studies without the financial concerns of eking out an everyday existence ... Set in the austerity of depression-era Tokyo, "Woman of Tokyo" presents the dilemma of moral responsibility, obligation, and perseverance in the increasing hopelessness of an economically polarized, modern Japan. Characteristic of his early films (such as "Record of a Tenement Gentlemen"), Yasujiro Ozu addresses contemporary social issues by examining the dissolution of family. [www.filmref.com]